Indian Fish Exports and Dependence on P. Vannamei: Share and Externalities - Shyam S. Salim; R. Geetha; Athira N.R. (Journal of Indian Fisheries Association, 2023)
Fishery products play a prominent role in contributing significantly for the success of the export scenario of India. India exported 13.8 lakh tonnes of seafood worth an all-time high of US $ 7.08 billion (₹ 45000 crores) in 2017-18. Amidst the global recession and economic meltdown, the sector performed well. Contrary to the major competitors' slowdown in export growth, the country's sea food trade grew by double digit in quantum as well as value. The introduction of P. vannamei has boosted the Indian exports and brought a sea change in the Indian shrimp production and processing industry. The production of vannamei had registered a hike from 2009-10 to 2017-18 (622327 t in 2017-18 compared to 1731 tonnes in 2009-2010) with a high productivity of 6.65 t ha-1 (MPEDA, 2010; MPEDA, 2019) and marked as one of the major reason for the performance of Indian export industry during the recession period. As an alternative to P. monodon, P. vannamei has completely resulted in achieving the goal of higher productivity and thereby increasing contribution in the export earnings. The present paper studied the significance of P. vannamei over other shrimps in the Indian fisheries export over the years with special focus on analysing the export performance in terms of trends and forecast of Indian frozen shrimp. The study also assessed the diﬀerent externalities associated with the P. vannamei. The results revealed that, frozen shrimp registered the highest growth rate in quantity from 3.15 per cent to18.95 per cent over the years. Forecasting results shows that India is becoming more and more a vannamei exporter leading to a one commodity exporter nation. Export profiling analysis validates the forecast result that P. vannamei holds the major share of 73 % of the total value of shrimp export which is about 50.36 % of the total export. A total of Rs.16000 crore is estimated as the total production externality associated with the production of P. vannamei and also there exists a high cost of importing brood stock for P. vannamei causing huge market risk and thereby declining the price by 30 %. The study advocates the need for accounting externalities in farming operations for the sustainable production of P.vannamei. Moreover strict implementation of scientific farming techniques, strengthening the alternate internal marketing and species diversification should be promoted in a consistent manner for enhancing the varied shrimp products and thereby the Indian shrimp export.